The Effect of the Finger-Holding Relaxation Technique on Pain Reduction in a Post-Appendectomy Patient at BLUD RSUD Kabupaten Buton: A Case Study - Sri Resky Mustafa; Nur Alifiah Ramadhani Asdar; Nurjannah (Journal Kiara : Nursing and Midwifery, 2026)
Background: Postoperative pain remains a frequent clinical problem following appendectomy and may interfere with recovery. Complementary non-pharmacological interventions are increasingly used to support pain management. The finger-holding relaxation technique is a simple relaxation method that may reduce pain perception. Objective: To describe the effect of the finger-holding relaxation technique on pain intensity in a post-appendectomy patient. Methods: This case study involved a 21-year-old patient experiencing acute pain after appendectomy. The finger-holding relaxation technique was administered once daily for three consecutive days. Pain intensity was assessed before and after the intervention using the Numeric Rating Scale (NRS). Results: A gradual decrease in pain intensity was observed following the implementation of the finger-holding relaxation technique over the three-day intervention period. Conclusion: The finger-holding relaxation technique may be considered an effective complementary nursing intervention for reducing postoperative pain in post-appendectomy patients.